Determination of Polypeptide Antibiotic Residues in Food of Animal Origin by Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry - Bladek, Tomasz (Molecules, 2020)
A novel UHPLC-MS/MS method for the determination of polypeptide antibiotic residues in animal muscle, milk, and eggs was developed and validated. Bacitracin A, colistin A, colistin B, polymyxin B1, and polymyxin B2 were extracted from the samples with a mixture of acetonitrile/water/ammonia solution 25%, 80/10/10 (v/v/v), and put through further evaporation, reconstitution, and filtration steps. The chromatographic separation was performed on a C18 column in gradient elution mode. Mass spectral acquisitions were performed in selective multiple reaction monitoring mode by a triple quadrupole mass spectrometer. The method was validated according to the criteria of Commission Decision 2002/657/EC. The method quantifies polypeptides in a linear range from 10 to 1000 μg kg(−1), where the lowest concentration on the calibration curve refers to the limit of quantification (LOQ). The recoveries ranged from 70 to 99%, the repeatability was below 13%, and within-laboratory reproducibility was lower than 15%. The decision limit (CCα) and detection capability (CCβ) values were calculated, and ruggedness and stability studies were performed, to fulfill the criteria for confirmatory methods. Moreover, the developed method may also be used for screening purposes by its labor efficiency.